APLIKASI PERPUSTAKAAN BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER (STUDI KASUS: SMPN 3 PACET) - Hendra Sopandi; Novita Anggraini (NUANSA INFORMATIKA, 2024)
The role of information technology is very beneficial for many industries. It is necessary for data to meet the needs of data users. Support in the field of education can be included in one of these fields. The library of SMPN 3 Pacet Bandung contains various textbooks and other complementary books. The library itself still uses a manual system in recording or bookkeeping for loan transactions, book returns, book checks, and library reports. Such a manual method is not possible, because the volume of transaction data is increasing, resulting in increased difficulty in processing library data. With these problems, SMPN 3 Pacet Bandung needs an information system to overcome the problems of using a manual system. This system is a web-based application using the codeigniter framework to facilitate the design of the system. The author hopes that making this library application can help the library more easily, effectively and efficiently for staff and all parties involved in library data processing.